2020
DOI: 10.1080/09712119.2020.1844714
|View full text |Cite
|
Sign up to set email alerts
|

Characterization in vitro of new bacterial strains showing potentially probiotic crossed effect against vibriosis in relevant fish species for marine aquaculture

Abstract: Real (2020) Characterization invitro of new bacterial strains showing potentially probiotic crossed effect against vibriosis in relevant fish species for marine aquaculture,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Previous in vitro and in vivo studies carried out with A. faecalis A12C demonstrated its probiotic crossed effect against vibriosis or Photobacterium damselae Subsp. piscicida in relevant sh species for marine aquaculture [18,19]. Recently, our research group has shown the potential probiotic effect of this strain in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro and in vivo studies carried out with A. faecalis A12C demonstrated its probiotic crossed effect against vibriosis or Photobacterium damselae Subsp. piscicida in relevant sh species for marine aquaculture [18,19]. Recently, our research group has shown the potential probiotic effect of this strain in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies by our group, a strain of Alcaligenes faecalis sub faecalis (A. faecalis A12C), isolated from Argyrosomus regius gills, have shown excellent conditions as potential probiotic in sh due to inhibitory activity against different pathogens, particularly, Photobacterium damselae subsp. piscicida and Vibrio anguillarum, stimulating their immune response by activating a variety of pro-in ammatory cytokines, such as interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) [4,19]. Our group reported the rst study examining the probiotic effects of A. faecalis A12C on general, biochemical, and pathological parameters in a clinically relevant rodent model of peritonitis showing that oral administration of this strain during 7 days is safe and had marked effects on the spread of infection [20].…”
Section: Introductionmentioning
confidence: 99%